IMPACT OF THE EFFECTIVE USE OF WORKING CAPITAL IN INDUSTRIAL ENTERPRISES ON FINANCIAL STABILITY (World Economics and Finance Bulletin, 2024)
In this article, the effect of effective use of working capital in industrial enterprises on financial stability is studied by the object of research. The state of use of working capital in ensuring the financial stability of industrial enterprises was analyzed, and scientific suggestions and recommendations were developed to increase the effect on financial stability through the effective use of working capital in industrial enterprises.
Keywords: financial stability; cash; normalization of working capital